2014
DOI: 10.1186/1556-276x-9-27
|View full text |Cite
|
Sign up to set email alerts
|

Ethylenediaminetetraacetic acid as capping ligands for highly water-dispersible iron oxide particles

Abstract: Monodispersed magnetite (Fe3O4) particles were synthesized using a high-temperature hydrolysis reaction with the assistance of ethylenediaminetetraacetic acid (EDTA) as capping ligands. These particles were composed of small primary nanocrystals and their sizes could be tuned from about 400 to about 800 nm by simply changing the EDTA or precursor concentration. Surface-tethered EDTA made the particles highly water-dispersible. The as-prepared magnetite particles also showed superparamagnetic behavior at room t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…The larger clusters of bare MNPs as compared to His-MNPs indicate that surface coating with L-His could stabilize MNPs, which might suppress their aggregation. 30 Thus, the results of AFM and SEM are in close agreement with each other. The SEM-EDS spectra ( Fig.…”
Section: Characterization Of His-mnpssupporting
confidence: 80%
“…The larger clusters of bare MNPs as compared to His-MNPs indicate that surface coating with L-His could stabilize MNPs, which might suppress their aggregation. 30 Thus, the results of AFM and SEM are in close agreement with each other. The SEM-EDS spectra ( Fig.…”
Section: Characterization Of His-mnpssupporting
confidence: 80%
“…Crystalline copper nanoparticles grown on carbonized chitosan without cross-linking (EDTA) in CuCS-700 or without using melamine in CuNC-700, display similar diffraction patterns, but giving a large crystal size of 48 nm and 37 nm, respectively. This confirms the proposed role of EDTA as a cross-linker to sequestrate the growing metal leading to high particles dispersion [39], and the use of the nitrogen for stabilizing smallsized metal species in the materials [40]. No copper oxides or other crystalline phase were observed, indicating selective formation of crystalline copper nanoparticles.…”
Section: Stp)supporting
confidence: 73%
“…Rahal et al [ 40 ] synthesized nickel oxide (NiO) nanoparticles capped with EDTA via co-precipitation method and results showed that EDTA capped nanoparticles were smaller in size as compared to the pure NiO nanoparticles with enhanced surface magnetization properties. EDTA was also employed in the synthesis of magnetic iron oxide nanoparticles to enhance the mono dispersion via high-temperature hydrolysis reaction resulting in more water solubility and enhanced magnetic properties [ 41 ].…”
Section: Introductionmentioning
confidence: 99%